Animal-borne video cameras reveal differences in northern fur seal foraging behavior related to prey size selection - Kuhn, Carey E.; Sterling, Jeremy T.; McCormley, Molly; Birkemeier, Burlyn; Sar, Angel; Flock, Audrey; Mordy, Calvin W. (Frontiers in Marine Science, 2022)
A key aspect of foraging ecology research is understanding how predator foraging behavior and success are influenced by variation in prey resources. For northern fur seals (Callorhinus ursinus), an understanding of predator-prey relationships is critical to help identify potential causes for the unexplained population decline in Alaska. To examine how foraging behavior differs based on prey size selection, we equipped northern fur seals on St. Paul and St. George islands (Alaska, USA) in September (2017, n=6) and August (2018, n=4, and 2019, n=3) with satellite-linked dive recorders and animal-borne video cameras. We categorized prey capture attempts based on relative prey size (small vs. large) and examined differences in capture depth, time of day, water temperature, and depth relative to the mixed-layer. Successful prey captures (n= 2224) primarily occurred at night (89.7 ± 3.1%) and small prey accounted for the majority of captures (70.5 ± 13.2%), but there was significant variation among individuals. Large prey were captured at nearly twice the depth of small prey (42.9 ± 3.7 m and 23.1 ± 1.8 m, respectively) and the proportion of large prey caught during the day was 3 times higher than at night (0.77 ± 0.1 vs. 0.25 ± 0.1). There was no relationship between prey size and water temperature after we accounted for temperature changes with depth. The highest proportion of prey captures occurred below the mixed-layer depth regardless of prey size, but the proportion of small prey captures above mixed-layer depth was double that of large prey. This enhanced understanding of northern fur seal prey capture behavior will be pivotal for better interpretation of decades of historical dive and diet data and can provide insight into how northern fur seals may respond to future variation in prey resources, which is essential to develop ecosystem-based approaches for northern fur seal conservation.